Smart distance alert system with Blynk integration for safer gadget use - Ismail, Syila Izawana; Ismail, Nuraiza; Mohd Zaki, Aisyah Hannah; Omar, Suziana; Mohamed, Syazilawati (Institute of Advanced Engineering and Science, 2024)
Gadgets have certainly become an integral part of our daily lives. From smartphones and tablets to laptops and smartwatches, we rely on these devices to stay connected, entertained, and productive throughout the day. Excessive usage of gadgets for a long time and unhealthy habits will lead to health problems such as myopia. Using gadgets at a close distance is one of the most common unhealthy habits among gadget users, especially children. This study, called